Inverse Association Between the Quantity of Human Peripheral Blood CXCR5+IFN-γ+CD8+ T Cells With De Novo DSA Production in the First Year After Kidney Transplant. Issue 11 (November 2020) - Zimmerer, Jason M.; Basinger, Matthew W.; Ringwald, Bryce A.; Abdel-Rasoul, Mahmoud; Pelletier, Ronald P.; Rajab, Amer; El-Hinnawi, Ashraf; Parekh, Hemant; Washburn, Kenneth; Bumgardner, Ginny L.
Abstract : Background: We recently reported that a novel CXCR5 + IFN-γ + CD8 + T-cell subset significantly inhibits posttransplant alloantibody production in a murine transplant model. These findings prompted the current study to investigate the association of human CD8 + T cells with the same phenotype with the development of de novo donor-specific antibody (DSA) after kidney transplantation. Methods: In the current studies, we prospectively and serially analyzed peripheral blood CD8 + and CD4 + T-cell subsets and monitored for the development of de novo DSA in kidney transplant recipients during the first-year posttransplant. We report results on 95 first-time human kidney transplant recipients with 1-year follow-up. Results: Twenty-three recipients (24.2%) developed de novo DSA within 1-year posttransplant. Recipients who developed DSA had significantly lower quantities of peripheral CXCR5 + IFN-γ + CD8 + T cells ( P = 0.01) and significantly lower ratios of CXCR5 + IFN-γ + CD8 + T cell to combined CD4 + Th1/Th2 cell subsets (IFN-γ + CD4 + and IL-4 + CD4 + cells; P = 0.0001) compared to recipients who remained DSA-negative over the first-year posttransplant. Conclusions: Our data raise the possibility that human CXCR5 + IFN-γ + CD8 + T cells are a homolog to murine CXCR5 + IFN-γ + CD8 + T cells (termed antibody-suppressor CD8 + T cells) and that the quantity of CXCR5 + IFN-γ + CD8 + T cells (or the ratio of CXCR5 + IFN-γ + CD8 + T cells to Th1/Th2 CD4 + T cells) may identify recipients at risk for development of DSA. Abstract : Supplemental Digital Content is available in the text.